Analisis Peran Batalyon B Pelopor Brimob Parepare dalam Operasi Penanganan Gangguan Keamanan Berintensitas Tinggi di Wilayah Konflik Bersenjata Papua - Amran; Muh. Tahir; Nurmiati Muhiddin; Muslihin (PT PUSTAKA CENDEKIA GROUP, 2024)
The purposes of this study are: 1) To analyze the process of implementing operational assistance in handling high-intensity security disturbances in Papua by Battalion B Pelopor Brimob Parepare, and 2) To analyze the factors that hinder the implementation of operational assistance in handling high-intensity security disturbances in Papua by Battalion B Pelopor Brimob Parepare. This type of research is empirical legal qualitative research. To obtain the data and information needed, the researcher chose the research location at Battalion B Pelopor Brimob Pare-pare which is located on Jl. Chalik No.3, Sumpang Minangae, Kec. Bacukiki Bar.Pare-pare City. The type of data used in this study was qualitative data consisting of primary data and secondary data. The conclusions of this study are 1) The process of implementing operational assistance by Battalion B Pelopor Brimob Parepare in handling high-intensity security disturbances in Papua were by: Identifying and analyzing the types of high-intensity security disturbances that occurred in Papua, Formulating appropriate operational strategies and plans to provide assistance in handling these security disturbances, Coordinating and mobilizing personnel and resources needed to carry out operations in the field, Monitoring and evaluating the effectiveness of actions taken in handling security disturbances, and Making adjustments and improvements to personnel capabilities and operational readiness on an ongoing basis. 2) Factors that hinder the implementation of operational assistance in handling high-intensity security disturbances in Papua by Battalion B Pelopor Brimob Parepare were: difficulty in coordinating with leaders of conflicting groups, lack of troops who will be on duty in Papua, and punishments that have not provided a deterrent effect.